82.3k views
2 votes
Simplify the polynomial (-8×)+×+(-2)​

2 Answers

5 votes

Answer:-7x-2

Explanation:

User Tmullaney
by
6.0k points
1 vote

Answer:

The correct answer is -9x

Explanation:

It is given a polynomial,

p(x) = (-8x) + x + (-2x)​

To simplify p(x)

p(x) = (-8x) + x + (-2x)​

= -8x + x - 2x

= -8x - 2x + x

= -10x + x

= -9x

(-8x) + x + (-2x)​ = -9x

Therefore the correct answer is -9x

User Jerry Stratton
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.